Predictors of Recurrence After Curative Surgery for Stage I Colon Cancer: Retrospective Cohort Analysis of the Italian Society of Surgical Oncology Colorectal Cancer Network Collaborative Group - Giulia Turri, MD; Luigi Martinelli, MD; Daniela Rega, MD; Nicolò Tamini, MD; Lucia Paiano, MD; Simona Deidda, MD; QuocRiccardo Bao, MD; Laura Lorenzon, MD, PhD; Raffaele De Luca, MD; Caterina Foppa, MD, PhD; Valentina Mari, MD; Giovanni Taffurelli, MD; et al. (Annals of Surgery Open)
Objective:. The aim of this study is to provide solid evidence to update the management of stage I colon cancer (CC) after surgery. Background:. Given the low risk of recurrence of stage I CC, some international guidelines do not recommend intensive follow-up after surgery. However, data on the actual incidence, risk factors, and site of recurrences are scarce. Methods:. This is a retrospective multicenter cohort study considering patients who underwent surgery at 25 Italian centers between 2010 and 2019, with a minimum follow-up of 24 months. A total of 1883 consecutive adult patients with stage I CC treated with curative surgery were considered, and 1611 fulfilled the inclusion criteria. The primary outcome was the rate of recurrence. Secondary outcomes included survival and risk factors for recurrence. Results:. Eighty patients developed cancer recurrence (5.0%), of which 90% was systemic relapse. The event was more frequent in pT2 (6.0% vs 3.2%, P = 0.013), male patients (6.1% vs 3.6%, P = 0.021), in the presence of lymphovascular invasion (7.2% vs 3.6%, P = 0.01), and in cases of partial resection (11.1% vs 4.6%, P = 0.011). Also, preoperative carcinoembryonic antigen (P = 0.007) and tumor diameter (P < 0.001) were higher in the group who relapsed. Most patients had isolated cancer recurrence (90%). Recurrences peaked between 10 and 18 months after surgery and declined over time. Adjusted Cox regression analysis identified tumor diameter, carcinoembryonic antigen level, lymphovascular invasion, male gender, and less than 12 analyzed lymph nodes as significant risk factors for worse recurrence-free survival. Conclusions:. This study showed that a not negligible rate of stage I CC recur after curative surgery. Most relapses occur at a single site within the first 3 years after surgery. This evidence could be used to optimize postoperative follow-up.